The successful resolution of bilateral recurrent shoulder dislocation with the bilateral shoulder open latarjet procedure: a case report - Kanesen, Kumarendran; Yeak, Raymond Dieu Kiat; Abdul Kahar, Johan; Mohd Nasir, Mohd Nizlan (Springer, 2023)
Recurrent shoulder dislocation is a common orthopedic condition, but bilateral involvement is rare and presents unique challenges in management. The Latarjet procedure is an effective surgical technique that addresses instability by creating a bony block on the anterior glenoid rim. This case highlights the successful management of bilateral recurrent shoulder dislocation using the bilateral shoulder open Latarjet procedure and emphasizes the importance of early intervention in such cases.